The Role of the Student Organization’s Language Division in Constructing a Language Environment for Enhancing Speaking Skills: A Qualitative Study at Al-Tibyan Institute - Lubis, Mhd Firdaus; El Tigani, Mohammed Abdulaziz Mohammed Ahmed (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2026)
This study examines the role of the Language Division within the student organization at Al-Tibyan Institute in fostering a language-rich environment to develop speaking skills. While prior research emphasizes teachers and formal instruction, this study highlights the division as a non-formal educational agent within institutional contexts. Using a qualitative descriptive-analytical approach through interviews, observation, and document analysis, it explores programs, implementation, and daily practices supporting communicative competence. Findings show the division organizes structured language activities, continuous monitoring, remedial support, and feedback strategies, effectively linking classroom learning with real-life use. Participating students demonstrate improvements in fluency, accuracy, confidence, and vocabulary. The study underscores the division’s strategic role in bridging theory and practice and offers a replicable, sustainable model for institutions aiming to enhance speaking skills through immersive, interactive, and student-centered language environments.